Hydrological Contribution toward Sea Water Intrusion Phenomenon in Terengganu, Malaysia - Muhammad Barzani, Gasim; Mohd Khairul Amri, Kamarudin; Azman, Azid; Mohd Ekhwan, Toriman; Haniff, Muhammad (2015)
A study was conducted at Paka River, Terengganu on determination of hydrological characteristics of Paka River at seven sampling stations. Sampling was started from the estuary of Paka River, and ended about 14 km away from the estuary as each station was 2 km apart from each other. Sampling was carried out at two different water tides (low and high water tides) and two durational variations which represented by the Northeast Monsoon (wet period) and the Southeast Monsoon (dry period). Hydrological measurements of river velocity, river width and river depth were measured by using specific equipment. River width was measured by using a rangefinder (model Bushnell 20-0001), river depth was measured by using a depth meter (model Speedtech SM5) and river velocity was measured by using a flow meter/current flow meter (model FP101). Water quality parameters such as conductivity, salinity, pH and total dissolved solids (TDS) were directly measured in the field by using a multiparameter YSI 556 meter. Analyses of sodium, sulphate and magnesium ions were performed according to the standard method of analysis by APHA and HACH. Primary data which consist of hydrological measurements and physicochemical properties of Paka River were measured and analyzed for each sampling stations. Physicochemical parameters which consist of pH, total dissolved solids, salinity, electrical conductivity, sodium, sulphate and magnesium concentrations were applied in order to determine the correlations with the influence of seawater movement and other factors to the water quality of Paka River. Overall, station 1 was showing the highest readings for most physicochemical parameters at both water tides during the first and second samplings. Stations 1 that were located at the downstream identified by high readings of most physicochemical parameters as compared to stations 7 which located at the upstream, is related to the effect of seawater movement during high tide. Higher readings of physicochemical parameters were also shown during dry season since freshwater flow from the upstream due to less rainfall intensity.